The Design And Responses Of Horses On Polimeric Composite Horseshoes - Syam, Bustami; Muttaqin, Maraghi; Tantono, Julius; Eddo, Eddo; Sandry, Febri (TALENTA Publisher, 2022)
Horseshoe is used to avoid the failures of horse's hooves due to extreme impact and wear loads. The horse's hooves are repeatedly subjected to loadings during walking, trotting, running and jumping. In this research, we introduce a newly developed horseshoes made of polymeric composite materials. The horseshoes are placed inside the leather boot; it is a specially designed for horse. The process of making horseshoes and horse boots were discussed and the responses of the horse shoes as well as horses were analyzed. The horses were subjected to a series of testing, e.g., walking, trotting, and running. The result of the tests indicate that horseshoes and horse boots are quite strong, light, and safe to be used on horses. The response of horses shows that the horseshoe and boots are quite comfortable for them. This can be seen because there are no significant behavioral changes of the horse before and after wearing the boot. After being used to, it was shown that there is no damage or crack of the horseshoe. Therefore, it can be concluded that the composite horseshoe is safe and good to be used as horseshoe material.